2019
DOI: 10.1038/s41598-019-39005-8
|View full text |Cite
|
Sign up to set email alerts
|

Covariance statistics and network analysis of brain PET imaging studies

Abstract: The analysis of structural and functional neuroimaging data using graph theory has increasingly become a popular approach for visualising and understanding anatomical and functional relationships between different cerebral areas. In this work we applied a network-based approach for brain PET studies using population-based covariance matrices, with the aim to explore topological tracer kinetic differences in cross-sectional investigations. Simulations, test-retest studies and applications to cross-sectional dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 72 publications
2
65
0
Order By: Relevance
“…Consequently, static FDG-PET images cannot be used to estimate metabolic connectivity within single subjects, greatly limiting their application as a disease biomarker (cf. Yakushev et al, 2017;Veronese et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, static FDG-PET images cannot be used to estimate metabolic connectivity within single subjects, greatly limiting their application as a disease biomarker (cf. Yakushev et al, 2017;Veronese et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These findings highlight the importance of the choice of the correct target to assess molecular connectivity. To date, only three studies have examined dopaminergic connectivity with the PET modality [13,44,45]. The first study targeted postsynaptic dopamine D2 receptors in control subjects but did not find significant correlations between the striatum and extrastriatal areas using IRCA with different ROIs which did not include the midbrain [44].…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a decrease in connectivity within the nigrostriatal pathway in patients with early Parkinson's disease [45]. The third study using 18 F-FDOPA PET in 52 healthy subjects aimed to assess the feasibility of graph theory analysis [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research have got investigated the evolution and management of co-operation in the prisoner"s problem and also various other types [14]. Spatial games are actually especially important to the research of malignancy development as cell duplication and useful resource rivals is localized at the time of cancerous growth [15,16]. For proposed research we formulated the classification as well as, investigation of statistics with game theory pixel rendering and set theory.…”
Section: Figure 1-representation Of Cancerous Brain Tumor [14]mentioning
confidence: 99%